2022
DOI: 10.3390/su14010527
|View full text |Cite
|
Sign up to set email alerts
|

Will the Governance of Non-State Shareholders Inhibit Corporate Social Responsibility Performance? Evidence from the Mixed-Ownership Reform of China’s State-Owned Enterprises

Abstract: Fulfilling social responsibilities in order to sustain development has increasingly become a strategic choice for companies. Good corporate governance can guarantee high corporate social responsibility performance. This paper selects state-owned enterprises listed on the Shanghai and Shenzhen A-Share market from 2013 to 2019 as samples and uses a panel data OLS regression model to empirically test the impact of the governance of non-state shareholders on the social responsibility performance of state-owned ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 69 publications
0
24
1
Order By: Relevance
“…The mixed-ownership reform of state-owned enterprises reappeared in the political posture of the top-level design. This introduced non-state-owned capital and assigned senior executives to actively participate in the governance of state-owned enterprises, which then, to a certain extent, alleviate the opportunistic behavior, such as the "owner absence" and "internal control", thereby improving the quality of corporate governance in state-owned enterprises [16]. Moreover, the "profit-seeking nature" of non-state-owned capital make nonstate-owned shareholders to supervise the management of state-owned enterprises, thereby improving corporate performance and increasing corporate value.…”
Section: Governance Of Non-state-owned Shareholders and Capital Struc...mentioning
confidence: 99%
See 2 more Smart Citations
“…The mixed-ownership reform of state-owned enterprises reappeared in the political posture of the top-level design. This introduced non-state-owned capital and assigned senior executives to actively participate in the governance of state-owned enterprises, which then, to a certain extent, alleviate the opportunistic behavior, such as the "owner absence" and "internal control", thereby improving the quality of corporate governance in state-owned enterprises [16]. Moreover, the "profit-seeking nature" of non-state-owned capital make nonstate-owned shareholders to supervise the management of state-owned enterprises, thereby improving corporate performance and increasing corporate value.…”
Section: Governance Of Non-state-owned Shareholders and Capital Struc...mentioning
confidence: 99%
“…Therefore, non-stateowned shareholders can effectively influence corporate capital structure adjustment decisions by appointing senior executives to participate in SOEs' governance. In addition, Zhang et al [16] find that non-state-owned shareholder' governance can improve the sensitivity of executive compensation performance; and Frank and Goyal [22] find that incentive compensation for executives is conducive to speed up the adjustment of capital structure. This also shows that through constraints and incentive effects, SOEs can reduce management opportunistic behavior, improve governance levels, and reduce adjusting costs, thereby affecting capital structure adjustment decisions.…”
Section: Governance Of Non-state-owned Shareholders and Capital Struc...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this environment, private enterprises will be more likely to choose projects with greater investment benefits rather than environmental governance to achieve local economic development goals. Conversely, when the degree of regional marketization is relatively high, the external economic and legal environment is better, there is less government intervention, and the local government pays more attention to the protection of the ecological environment (Zhang et al, 2022). At this time, the introduction of state-owned participation shareholders by private enterprises will not only improve the governance structure and supervision mechanism of the enterprises but also their business objectives and development strategies will be improved with the entry of state-owned participation shareholders with environmental protection obligations, prompting them to make more environmental investments.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Although some studies have found that the board of directors of SOEs, being influenced by a traditional bureaucratic system, shows characteristics such as hierarchy recognition and benefits from the strong rank order of a "quasi-official" status, which in turn reduces the barriers to innovative risk decisions for high-level directors (Zhang et al, 2022a), these studies overlook a significant contradiction: SOEs often represent the interests of the state, beyond pursuing economic benefits, the motivation behind board decisions tends to focus more on stabilizing the economy, regulating the market, and ensuring employment among other societal performances (Sun et al, 2018;Zhang et al, 2022b). Therefore, the boards of SOEs bear more abundant political responsibilities (Bhat et al, 2020).…”
Section: Moderating Effect Of Property Rights Naturementioning
confidence: 99%